Membrane Cholesterol Affects Stimulus‐Activity Coupling in Type 1, but not Type 2, CCK Receptors: Use of Cell Lines with Elevated Cholesterol. Issue 3 (11th January 2013) - Harikumar, Kaleeckal G.; Potter, Ross M.; Patil, Achyut; Echeveste, Valerie; Miller, Laurence J.
Abstract: The lipid microenvironment of membrane proteins can affect their structure, function, and regulation. We recently described differential effects of acute modification of membrane cholesterol on the function of type 1 and 2 cholecystokinin (CCK) receptors. We now explore the regulatory impact of chronic cholesterol modification on these receptors using novel receptor‐bearing cell lines with elevated membrane cholesterol. Stable CCK1R and CCK2R expression was established in clonal lines of 25RA cells having gain‐of‐function in SCAP [sterol regulatory element binding protein (SREBP) cleavage‐activating protein] and SRD15 cells having deficiencies in Insig‐1 and Insig‐2 enzymes affecting HMG CoA reductase and SREBP. Increased cholesterol in the plasma membrane of these cells was directly demonstrated, and receptor binding and signaling characteristics were shown to reflect predicted effects on receptor function. In both environments, both types of CCK receptors were internalized and recycled normally in response to agonist occupation. No differences in receptor distribution within the membrane were appreciated at the light microscopic level in these CHO‐derived cell lines. Fluorescence anisotropy was studied for these receptors occupied by fluorescent agonist and antagonist, as well as when tagged with YFP. These studies demonstrated increased anisotropy of the agonist ligand occupying the active state of the CCK1R in a cholesterol‐enriched environment, mimicking fluorescence of the uncoupled, inactive state of this receptor, while there was no effect of increasing cholesterol on fluorescence at the CCK2R. These cell lines should be quite useful for examining the functional characteristics of potential drugs that might be used in an abnormal lipid environment.